A blockchain-enabled solution to enhance security in industrial control system - Ong, Ding Sheng (Nanyang Technological University, 2021)
Industrial Control Systems (ICS) are widely used across different industries such as power grid, water treatment, and nuclear power plants. ICS serves as a backbone of critical infrastructure. They are interconnected cyber-physical systems (CPS) that function as both monitoring and controlling systems. As such, most ICS controllers do not have authentication features or support encrypted communication. Moreover, they are rarely or never patched. With the advancements in technology, the level of connectivity has become more complex, and such complexity has exposed the system to potential cybersecurity threats. In this project, we will be proposing a Blockchain-based solution to enhance the security in ICS. The solution involves improvising the concept of Blockchain and integrating it into ICS to achieve a robust security network. In this project, we focused on the power grid, using it as a sample to prove the concept by using Raspberry Pi. Research and experiment were also done mainly on the power grid system components such as a substation, transmission, and relays. These components are the key features that have a direct impact on the operation of the power grid. Insights from the research and experiment results will serve as concrete supporting documents for future research or even implementation.